Konferensi Inter-Indonesia Tahun 1949: Wujud Konsensus Nasional antara Republik Indonesia dengan Bijeenkomst voor Federaal Overleg - Widhi Setyo Putro (Jurnal Sejarah Citra Lekha, 2018)
This article discusses the national consensus between the Republic of Indonesia (RI) and the Bijeenkomst voor Federaal Overleg (BFO) which embodied in the 1949 Inter-Indonesia Conference. Using conflict and consensus theory of Ralf Dahrendorf, this article seeks to understand the conflicts of interest background and the process towards a consensus between RI and BFO. The conflict between RI and BFO motivated by the Dutch aimed to control Indonesia. One of his efforts was to divide the Indonesian nation by forming states, which led to a conflict between the Republicans (Republicans) who supported the united state, and the federalists (BFO) in favor of the federal state. The study found that the Dutch federal policy was not entirely a success because the federalists which incorporated in BFO was not affected. The conflict between the Republican and federalists subsided with the implementation of the Goodwill Mission and the sending of the BFO Liaison Commission to meet Indonesian leaders detained after the Dutch Military Aggression II. The summit was a national consensus between RI and BFO, it embodied in the Inter-Indonesia Conference in 1949 which took placed at Yogyakarta and Jakarta. They reached a consensus by agreeing on fundamental issues as the identity of a sovereign state, such as the name of the country, Merah Putih as the official flag, Bahasa Indonesia as the official language, and the Indonesia Raya as the national anthem.